تخدير مرضى الآفات الرئوية الإنسدادية المزمنة - ابراهيم, رزق الله; الخير, محمد; خليل, زهير (Latakia University Journal -Medical Sciences Series, 2019)
أجريت الدراسة في مشفى الأسد الجامعي في اللاذقية في قسم التخدير والإنعاش على /60/ مريض مصاب بآفة رئوية انسدادية مزمنة خلال العام 2005-2006. تم تقسيم هؤلاء المرضى إلى مجموعتين: مجموعة أولى: تضمنت /30/ مريض أجريت لهم الجراحة المقررة تحت التخدير العام. مجموعة ثانية: تضمنت /30/ مريض أجريت لهم الجراحة المقررة تحت التخدير الناحي. كانت النتائج على الشكل الآتي: 1- حدث نقص أكسجة في أثناء المباشرة عند 10% من مرضى التخدير العام. 2- حدث نقص أكسجة في أثناء الصحو عند 20% من مرضى التخدير العام. 3- حدث احتباس CO2 في أثناء الصحو عند 26% من مرضى التخدير العام. 4- حدث تشنج قصبي في أثناء الصحو عند 40% من مرضى التخدير العام. 5- حدث سعال في أثناء الصحو عند 35% من مرضى التخدير العام. 6- حدث تغيرات ذات أهمية في قيم غازات الدم الشريانية عند 30% من مرضى التخدير الناحي. This study was carried out in 2005-2006 in the department of Anesthesia at AL-Assad University Hospital in Lattakia and included /60/ patients affected with chronic obstructive pulmonary diseases. Patients were classified into two groups: The first group included /30/ patients how were undergone selective surgery by using general anesthesia. The second group included /30/ patients operated on by using general anesthesia. The results were as follows: 1- 10% of patients with general anesthesia have experienced hypoxia of during induction. 2- 20% of patients with general anesthesia have experienced hypoxia of during recovery. 3- 26% of patients with general anesthesia have CO2 retention during recovery. 4- 40% of patients with general anesthesia have broncho-spasm during recovery. 5- 35% of patients with general anesthesia have experienced coughing during recovery. 6- 30% of patients with local anesthesia have shown remarkable changes in the arterial blood gasses values.